2020
DOI: 10.3389/fpubh.2020.580327
|View full text |Cite
|
Sign up to set email alerts
|

Global Forecasting Confirmed and Fatal Cases of COVID-19 Outbreak Using Autoregressive Integrated Moving Average Model

Abstract: The world health organization (WHO) formally proclaimed the novel coronavirus, called COVID-19, a worldwide pandemic on March 11 2020. In December 2019, COVID-19 was first identified in Wuhan city, China, and now coronavirus has spread across various nations infecting more than 198 countries. As the cities around China started getting contaminated, the number of cases increased exponentially. As of March 18 2020, the number of confirmed cases worldwide was more than 250,000, and Asia alone had more than 81,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Nemes and Kiss [ 21 ] performed a sentiment analysis of social media based on COVID 19 (comments, hashtags, posts, tweets). While COVID-19 outbreak had an effect over the world [ 22 , 23 ], the study considered recurrent neural networks (RNN) for the analysis. The study concluded that there are more positive tweets over social media.…”
Section: Methodsmentioning
confidence: 99%
“…Nemes and Kiss [ 21 ] performed a sentiment analysis of social media based on COVID 19 (comments, hashtags, posts, tweets). While COVID-19 outbreak had an effect over the world [ 22 , 23 ], the study considered recurrent neural networks (RNN) for the analysis. The study concluded that there are more positive tweets over social media.…”
Section: Methodsmentioning
confidence: 99%
“…If we combine autoregressive and moving average models, we will get a non-seasonal ARIMA model ( 35 ). In the autoregressive model, the linear combination of past values of variables is used to predict interesting variables in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Singh et al [56] used a moving area model to predict the COVID-19 pandemic for the top 15 affected nations, where cumulative cases, deaths, and recoveries from COVID-19 were compared among the United States, the United Kingdom, Turkey, China, Russia, Switzerland, Germany, Iran, Brazil, the Netherlands, Italy, France, Germany, and Spain. On the other hand, Dansana et al [57] explored the fatal cases of the pandemic outbreak using a moving average (MA) model and forecasted the cases of COVID-19 in the future by successfully calculating the total confirmed cases and fatalities over the studied dates. As reported by Pal et al [58], the MA model provides a sparing description of a stationary stochastic process in terms of a polynomial.…”
Section: Literature Reviewmentioning
confidence: 99%